POLA KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA KEPALA DESA MARAO KECAMATAN ULUNOYO KABUPATEN NIAS SELATAN - Fidderman Gori; Prietsaweny RT Simamora (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study aims at determining at the patterns and processes of organizational communication between village heads and village officials in improving the performance of village government, and what factors are the obstacles in the organizational communication process between village heads and officials. as well as tools and instruments in improving village government performance. The method used in this research is descriptive qualitative method. The results show that the communication pattern and process used was the total channel pattern, which gave freedom to convey information from both the village head and village officials and village officials to the village head. The inhibiting factor is the miscommunication that occurs between the village head and village officials and vice versa semantic and physical obstacles.